Prosedur Pengajuan Dan Realisasi Kredit Pada KSP Kopdit Hiro Heling Cabang Utama - Veronika Febronia; Emilianus Eo K.Goo (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The aim of this research is to determine the procedures for applying for and realizing credit at KSP Kopdit Hiro Heling. Research data was obtained through direct interviews with the head of the credit division, training and promotion, observation and documentation. This type of research is descriptive qualitative. The results of the research show that loan service procedures have been running well by following established standard procedures and are very helpful in the credit distribution process in cooperatives.